Intraoperative radiotherapy for breast cancer treatment efficiently targets the tumor bed preventing breast adipose stromal cell outgrowth - Uhlig, Stefanie; Wuhrer, Anne; Berlit, Sebastian; Tuschy, Benjamin; Sütterlin, Marc; Bieback, Karen (Strahlentherapie und Onkologie, 2020)
Mesenchymal stromal cells (MSC) in bone marrow have been shown to be radioresistant, which is related to pronounced DNA repair mechanisms. Intraoperative radiotherapy (IORT) during breast-conserving surgery for early breast cancer is an innovative technique applying low energy x‑ray to the tumor bed immediately after removal of the tumor. IORT is considered to reduce the risk of local tumor recurrence by directly targeting cells of the tumor bed and altering the local microenvironment. Aim of this study was to investigate whether IORT affects the outgrowth potential of breast adipose tissue-derived MSC (bASC) as part of the tumor bed.